Contemporary Confucianism in Thought and Action - Alitto, Guy.; Alitto, Guy. (China Academic Library,, 2015)
This volume focuses on contemporary Confucianism, and collects essays by famous sinologists such as Guy Alitto, John Makeham, Tse-ki Hon and others. The content is divided into three sections – addressing the “theory” and “practice” of contemporary Confucianism, as well as how the two relate to each other – to provide readers a more meaningful understanding of contemporary Confucianism and Chinese culture. In 1921, at the height of the New Culture Movement’s iconoclastic attack on Confucius, Liang Shuming (梁漱溟) fatefully predicted that in fact the future world culture would be Confucian. Over the nine decades that followed, Liang’s reputation and the fortunes of Confucianism in China rose and fell together. So, readers may be interested in the question whether it is possible that a reconstituted “Confucianism” might yet become China’s spiritual mainstream and a major constituent of world culture.